Who is Francesca da Rimini? Problems of Historical Reception - Uricchio, William; Pearson, Roberta (Cinémas, 1992)
This paper uses intertextuel evidence to approach the vexed topic of historical reception, focusing upon the ways in which certain groups of hypothetical readers may have made sense of Vitagraph's Francesca da Rimini (1908), a film based upon five lines of Dante. The authors hope to demonstrate that supplementing formal textual analysis and industry discourse with intertextual evidence can more fully illuminate conditions of reception by permitting speculation about historically grounded readings of specific texts.